An Approach to Incorporate Rock Fabric Information in Blast Fragmentation Investigations - Dirk van Zyl (International Society of Explosives Engineers, 1986)
Rock fabric information is often available from drill hole information and bench face mapping. An approach is presented to predict fragment size distribution of blasted material from this information as well as that obtained after the blast. The following information available from a mineral exploration drilling program was used in the prediction of fragment size distribution: largest piece, percent particles larger than 1 inch and RQD. Photographs of bench faces were used to estimate the fragment size distribution. Fracture spacings were evaluated along a series of parallel lines on the photograph. Photographic techniques were also used to obtain the grain size distribution of blasted material. m is paper describes the methodologies applied in some detail.